20 years of the European IVF-monitoring Consortium registry: what have we learned? A comparison with registries from two other regions. Issue 12 (14th November 2020) - De Geyter, Ch; Wyns, C; Calhaz-Jorge, C; de Mouzon, J; Ferraretti, A P; Kupka, M; Nyboe Andersen, A; Nygren, K G; Goossens, V
Abstract: STUDY QUESTION: How has the performance of the European regional register of the European IVF-monitoring Consortium (EIM)/European Society of Human Reproduction and Embryology (ESHRE) evolved from 1997 to 2016, as compared to the register of the Centres for Disease Control and Prevention (CDC) of the USA and the Australia and New Zealand Assisted Reproduction Database (ANZARD)? SUMMARY ANSWER: It was found that coherent and analogous changes are recorded in the three regional registers over time, with a different intensity and pace, that new technologies are taken up with considerable delay and that incidental complications and adverse events are only recorded sporadically. WHAT IS KNOWN ALREADY: European data on ART have been collected since 1997 by EIM. Data collection on ART in Europe is particularly difficult due to its fragmented political and legal landscape. In 1997, approximately 78.1% of all known institutions offering ART services in 23 European countries submitted data and in 2016 this number rose to 91.8% in 40 countries. STUDY DESIGN, SIZE, DURATION: We compared the changes in European ART data as published in the EIM reports (2001–2020) with those of the USA, as published by CDC, and with those of Australia and New Zealand, as published by ANZARD. PARTICIPANTS/MATERIALS, SETTING, METHODS: We performed a retrospective analysis of the published EIM data sets spanning the 20 years observance period from 1997 to 2016, together with the published data sets of the USA as well as of Australia and New Zealand. By comparing the data sets in these three large registers, we analysed differences in the completeness of the recordings together with differences in the time intervals on the occurrence of important trends in each of them. Effects of suspected over- and under-reporting were also compared between the three registers. X 2 log-rank analysis was used to assess differences in the data sets. MAIN RESULTS AND THE ROLE OF CHANCE: During the period 1997–2016, the numbers of recorded ART treatments increased considerably (5.3-fold in Europe, 4.6-fold in the USA, 3.0-fold in Australia and New Zealand), while the number of registered treatment modalities rose from 3 to 7 in Europe, from 4 to 10 in the USA and from 5 to 8 in Australia and New Zealand, as published by EIM, CDC and ANZARD, respectively. The uptake of new treatment modalities over time has been very different in the three registers. There is a considerable degree of underreporting of the number of initiated treatment cycles in Europe. The relationship between IVF and ICSI and between fresh and thawing cycles evolved similarly in the three geographical areas. The freeze-all strategy is increasingly being adopted by all areas, but in Europe with much delay. Fewer cycles with the transfer of two or more embryos were reported in all three geographical areas. The delivery rate per embryo transfer in thawing cycles bypassed that in fresh cycles in the USA in 2012, in Australia and New Zealand in 2013, but not yet in Europe. As a result of these changing approaches, fewer multiple deliveries have been reported. Since 2012, the most documented adverse event of ART in all three registers has been premature birth (<37 weeks). Some adverse events, such as maternal death, ovarian hyperstimulation syndrome, haemorrhage and infections, were only recorded by EIM and ANZARD. LIMITATIONS, REASONS FOR CAUTION: The methods of data collection and reporting were very different among European countries, but also among the three registers. The better the legal background on ART surveillance, the more complete are the data sets. Until the legal obligation to report is installed in all European countries together with an appropriate quality control of the submitted data the reported numbers and incidences should be interpreted with caution. WIDER IMPLICATIONS OF THE FINDINGS: The growing number of reported treatments in ART, the higher variability in treatment modalities and the rising contribution to the birth rates over the last 20 years point towards the increasing impact of ART. High levels of completeness in data reporting have been reached, but inconsistencies and inaccuracies still remain and need to be identified and quantified. The current trend towards a higher diversity in treatment modalities and the rising impact of cryostorage, resulting in improved safety during and after ART treatment, require changes in the organization of surveillance in ART. The present comparison must stimulate all stakeholders in ART to optimize surveillance and data quality assurance in ART. STUDY FUNDING/COMPETING INTEREST(S): This study has no external funding and all costs are covered by ESHRE. There are no competing interests. TRIAL REGISTRATION NUMBER: N/A.